2017
DOI: 10.1002/app.45033
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated shape memory behavior of melt‐mixed polyurethane/cellulose nanocrystal composites

Abstract: Building blocks made from renewable sources attract increasing attention for the design of new polymer systems. Recently, in this particular context, cellulose nanocrystals (CNCs) have gained great interest in both academic research and industry, mainly on account of their ability to reinforce range of polymer matrices and afford nanocomposites with attractive mechanical properties. The limited thermal stability of conventionally produced cellulose nanocrystals (CNCs) has, however, so far limited the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 73 publications
3
49
0
Order By: Relevance
“…As well, the minute variability within the mechanical properties obtained from tension testing led to the assumption of a high level of dispersion, as seen in the similar study by Rueda et al 52 Furthermore, research has shown the benefit of adding CNCs to a polymeric matrix for mechanical tunability. 40,53,54 Consequently, when tested dry, the samples demonstrated a drastic increase in modulus as shown in previous work, 40,[55][56][57] but significantly out of the accepted range. To mitigate this increase, the samples were swollen to reach the needed range of moduli, since the presence of CNCs in the composite increased the hydrophilicity, allowing for the absorption of water.…”
Section: Discussionsupporting
confidence: 80%
“…As well, the minute variability within the mechanical properties obtained from tension testing led to the assumption of a high level of dispersion, as seen in the similar study by Rueda et al 52 Furthermore, research has shown the benefit of adding CNCs to a polymeric matrix for mechanical tunability. 40,53,54 Consequently, when tested dry, the samples demonstrated a drastic increase in modulus as shown in previous work, 40,[55][56][57] but significantly out of the accepted range. To mitigate this increase, the samples were swollen to reach the needed range of moduli, since the presence of CNCs in the composite increased the hydrophilicity, allowing for the absorption of water.…”
Section: Discussionsupporting
confidence: 80%
“…[47][48][49][50] CNCs have been used either as a switching element [51][52][53][54] or to reinforce polymers with intrinsic shape-memory effect, including a few polyurethanes. [55][56] We here report tailoring the properties of a commercially available [57][58][59][60] and widely investigated shape-memory poly(ester urethane) [61][62][63] containing crystallizable poly(1,4-butylene adipate) soft/switching segments and hard segments composed of 4,4-methylenediphenyl diisocyanate (MDI) and 1,4-butanediol. By formulating nanocomposites with CNCs and/or influencing the crystallization of the polyester segments via the addition of a nucleating agent we were able to increase the tensile storage modulus from 150 MPa (neat polymer) to 572 MPa, improve the shape fixity at a specific fixing temperature from 47 to 75% and increase the fixing temperature from 10 to 25 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…Various processing schemes have been used to reinforce both polar and nonpolar polymer matrices with CNCs, such as direct melt‐mixing, solvent casting from a common solvent, or the template approach . The latter approach permits one to kinetically trap a percolating CNC scaffold by solvent‐exchange from an aqueous CNC dispersion to an organic medium and impregnating the resulting organogel with a solution of a polymer of choice, which typically results in nanocomposites with exceptional mechanical properties in comparison to the other processing approaches.…”
Section: Introductionmentioning
confidence: 99%